A Territorial History of Central European Literature as a Literary and Cultural Legacy of the Habsburg Monarchy - Németh Vítová, Lenka (Porównania, 2021)
Martin C. Putna in 2018 published Obrazy z kulturních dějin Střední Evropy [Images from the Cultural History of Central Europe], in which he presents a spectacular panorama of the multiculturalism, multilingualism, and multiconfessionalism of the individual regions of Central Europe (which he understands as the cultural legacy of Austria-Hungary) in order to sketch their "histories of ideas" that allow for a fuller reflection on the past and thus for building a future based on these (forgotten or sometimes suppressed) experiences. By proposing a territorial history of literature, the author gives a new direction to the closed-circle discussion of the construct of Central Europe: the essayistic images - despite their fragmentary and subjective readings - are clearly a step towards treating literature and culture as a medium of memory, counting on the causal effect of the memory they retain (after Astrid Erll genitivus objectivus).